Integration of Service Learning in Higher Education Institutions (HEIs) and Volunteerism in Communities: The Cases of 2018 Summer Season Voluntarism in Amhara Region - Jerusalem Yibeltal Yizengaw; Asnake Tarekegn Nigussie (Randwick International of Social Science Journal, 2020)
Among the classic roles of Higher Education Institutions (HEIs) i.e., research, teaching and community service the social engagement of institutions and their impact on civil society should be particularly highlighted. Of which, volunteering and service learning are believed to be an excellent means for accomplishing such goals. However, whether or not HEIs in developing countries like Ethiopia are able to materialize their social responsibility through such activities like student volunteerism, and their role in developing the active society was least explored. As a result, this study was planned to take place with a major objective to explore the integration of Service Learning in HEIs and Services in communities with a special focus to the cases of 2018 Summer Youth Voluntarism in Amhara Region of Ethiopia. For the purpose, a qualitative research methodology was employed. Officers and experts in the Amhara Region Bureau of Youth and Sports, and similar others at Bahir Dar City Zonal administration and in the sub-cities were drawn as informants and drawn data through interviews. In addition, the role of universities in promoting Service learning was examined from the syllabuses point of view, mainly a Course called Civics & Ethical Education using a content analysis technique. The findings reveal that though the service learning in the HEIs was not much visible through the Harmonized curriculum, Youth, especially, students of HEIs in Amhara Region of Ethiopia were found to be fully participated in services of community during the summer season of 2018, which implies the availability of the required motivation from the youth side. However a well-developed integration of service learning and volunteerism was unable to be discovered rather, this study calls for its realization.